2018
DOI: 10.2351/1.5038052
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oxide layer on adhesion and durability of titanium and transparent polyamide joint by laser joining

Abstract: A joint of titanium and transparent polyamide with desirable strength was achieved by laser joining. A maximum load capacity of 3400 N was obtained from a lap joining area of 25 × 25 mm2 at a laser power of 350 W and a travel speed of 4 mm/s. The effects of surface oxide layers with different thicknesses and stability were investigated. A joint with a thick oxide layer exhibited lower load capacity due to excessive thermal degradation of polyamide caused by heat buildup inside the thick thermal insulating oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…A method for treating metal surfaces to enhance adhesion is chemical treatment [34,35]. The authors [36] showed that the thickness of the oxide layer significantly influences the mechanical characteristics of the bond. The titanium/polyamide bond with a thick oxide layer showed lower load capacity, and with UV irradiation, a more pronounced decrease in bond strength was observed.…”
Section: Introductionmentioning
confidence: 99%
“…A method for treating metal surfaces to enhance adhesion is chemical treatment [34,35]. The authors [36] showed that the thickness of the oxide layer significantly influences the mechanical characteristics of the bond. The titanium/polyamide bond with a thick oxide layer showed lower load capacity, and with UV irradiation, a more pronounced decrease in bond strength was observed.…”
Section: Introductionmentioning
confidence: 99%
“…A method for treating metal surfaces to enhance adhesion is chemical treatment [29,34]. The authors [35] showed that the thickness of the oxide layer significantly influences the mechanical characteristics of the bond. The titanium/polyamide bond with a thick oxide layer showed lower load capacity, and with UV irradiation, a more pronounced decrease in bond strength was observed.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Chanthapan et.al. [29] investigated the effects of titanium oxide layer on the strength and durability of laser welded titanium polyamide joints. However, laser treatment of Ti64 prior to laser welding with polymers has been neglected in literature and the effects of laser pretreatment parameters on joint behaviors remain unclear.…”
Section: Introductionmentioning
confidence: 99%